Exploring the Lived Experiences of Individuals with Tattoos - Lucas, Tesha (East Carolina University, 2009)
The purpose of this qualitative phenomenological study was to explore and understand the perceived meaning of tattoo(s) for individuals with tattoos and the decisions, dimensions, and intentions related to the tattooing experience within the context of the participants' lived experiences. The qualitative findings resulted from two in-depth, open-ended interviews with each of six participants who addressed various aspects of tattooing, including the meaning of their tattoo(s) and decision points and motivations associated with their tattooing experiences. In conjunction with the one-on-one interviews, participants viewed photographs of their tattoos while sharing their stories and completed a lifeline document on which they indicated significant events in their lives, including obtaining their tattoo(s). The researcher coded, categorized, and identified patterns and themes in the verbatim transcriptions of the interviews. Themes that emerged from the data included a shift in thinking regarding tattoos, the tattooing experience, meaning of tattoos, tattoo presentation, the benefits of tattoo(s), desire to continue getting tattoos, and tattooing advice. The emergent themes created a foundation for understanding the lived experience of being tattooed including the decisions associated with the tattooing experience and health concerns and adverse reactions associated with tattooing. The Theory of Planned Behavior provided a foundation for discussing the findings of this study. The findings supported the existing literature regarding motivations for getting tattoos and meanings associated with tattoos, while extending the research about the tattooing experience. Findings also led to implications for the discipline and future research. Researchers and educators may use the findings from this study to assist in the development of effective strategies for modifying behaviors associated with tattooing within the theoretical framework of the Theory of Planned Behavior.
Keywords: Education, Health; Health education; Phenomenology; Qualitative; Tattoos; Tattooing; Self-perception; Identity (Philosophical concept)